Quantitative Map of Proteome Dynamics during Neuronal Differentiation - Christian K. Frese; Marina Mikhaylova; Riccardo Stucchi; Violette Gautier; Qingyang Liu; Shabaz Mohammed; Albert J.R. Heck; A.F. Maarten Altelaar; Casper C. Hoogenraad (Cell Reports, 2017)
Neuronal differentiation is a multistep process that shapes and re-shapes neurons by progressing through several typical stages, including axon outgrowth, dendritogenesis, and synapse formation. To systematically profile proteome dynamics throughout neuronal differentiation, we took cultured rat hippocampal neurons at different developmental stages and monitored changes in protein abundance using a combination of stable isotope labeling and high-resolution liquid chromatography-tandem mass spectrometry (LC-MS/MS). Almost one third of all 4,500 proteins quantified underwent a more than 2-fold expression change during neuronal differentiation, indicating extensive remodeling of the neuron proteome. To highlight the strength of our resource, we studied the neural-cell-adhesion molecule 1 (NCAM1) and found that it stimulates dendritic arbor development by promoting actin filament growth at the dendritic growth cone. We anticipate that our quantitative map of neuronal proteome dynamics is a rich resource for further analyses of the many identified proteins in various neurodevelopmental processes.